A Novel Optimal Time Window Determination Approach for ISAR Imaging of Ship Targets - Rui Cao; Yong Wang; Chunmao Yeh; Yun Zhang; Xiaofei Lu (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2022)
A well-focused and high-resolution inverse synthetic aperture radar (ISAR) image of ship target is appropriate to the target classification and recognition, especially for the ISAR image presenting the ship's top or side view. For this purpose, a novel optimal time window determination (OTWD) approach based on the imaging projection plane (IPP) selection is proposed in this article. First, the proposed OTWD approach determines the view of ship target in the ISAR image via the IPP selection. Then, the Doppler frequency is estimated via the time-frequency distribution (TFD) calculation for the azimuth signal of one scatterer. For the case of one range bin with multiple scatterers, a novel TFD extraction approach based on the clustering analysis is proposed. Afterward, the Doppler frequency is analyzed with sharpness to determine the optimal imaging time window, which can ensure the high image quality and optimal azimuth resolution. The proposed OTWD method is verified as accurate and effective with the experiments on simulated and real measured data.